PENGARUH TINGKAT PENDIDIKAN, PENGALAMAN KERJA, INSENTIF DAN KOMITMEN ORGANISASI TERHADAP KINERJA PENGELOLA KEUANGAN PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) KABUPATEN INDRAGIRI HILIR - Rohida Utami Monats; Hardi '; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research purposes was to determined the effects of education, work experience, incentives and organization commitment to financial performance on Local Work Unit (Satuan Kerja Perangkat Daerah (SKPD)) at Indragiri Hilir District. Sample in this study is the civil servants who work in the financial section in the units of Indargiri Hilir District. The number of samples taken from each SKPD 120 people. The results showed that the level of education affect the financial performance management. This is evidenced by t count (2.648) > t table (1.66342) with significant (0.000) < (0,05) for the variable levels of education. The fact is that higher education can help in improving analytical and problem solving skills. Work experience affect the financial performance management, as evidenced by the t count (6592) > t table (1.66342) with significant (0.0010) < (0,05) for variable work experience. Work experience will have a positive impact as experienced civil servants will be given a wider variety of tasks that already done so having the ability to complete the tasks assigned and the achievement of performance in terms of financial management. Incentives affect to the financial performance management, ha is evidenced by such t count value (2.770) > t table (1.66342) with significant (0.039) < (0.05). Incentives will have a positive impact as an additional revenue. Civil servant got more motivations in achieving tasks. Organizational Commitment affect the financial performance management, this is evidenced by t count (6784) > t table (1.66342) with significant (0.007) < (0.05). commitment of employees against institutions where they work will improve the financial performance management.Keyword : Education, work experience, incentives, and organization commitme